Quo Vadis: Pemberlakuan Undang – Undang Nomor 1 Tahun 2022 Terhadap Keberadaan Pajak Daerah Kota Padang - Fajri Kurniawan; Frenadin Adegustara; Gusminarti (Fakultas Hukum Universitas Andalas, 2023)
The existence of financial relations between the central government and regional governments is an embodiment of the concept of delegating authority from the central government to regional governments which is referred to as